Endodontic-Periodontal Interrelationship, a phenomenon dealt with dilemma: a Review (Bangladesh Journal of Dental Research & Education, 2013)
The term perio-endo lesion has been established to describe any lesion caused by any inflammatory product found in varying degrees in both the periodontium and the pulpal tissues and this inter-relationship between periodontal and pulpal disease was first described by Simring and Goldberg in 1964. As the pulpal and periodontal tissues have close embryonic, anatomical and functional inter-relationship; so, simultaneous existence of pulpal problems and inflammatory periodontal disease can be found frequently. This certainly can complicate diagnosis and also influencing outcome of treatment planning. A perio-endo lesion can have a varied pathogenesis which ranges from quite simple to relatively most complex one, thus coming to a definitive diagnosis a hard judged one. Having a thorough knowledge over these disease processes plays a key role in coming to the correct diagnosis and also subsequent treatment planning. This certainly can be achieved by careful history taking, a thorough intra and extra oral examination and the use of modern day special test apparatuses. Radiographic evaluations can also aid in clarifying the nature of the problem, even modern day Radio-Visio Graph or, RVG can also be a great tool that can come into aid. The prognosis and treatment of each endo-perio disease type varies a lot. Stating so, primary periodontal disease with secondary endodontic involvement and true combined endodontic-periodontal diseases require both endodontic and periodontal therapies along with proper medication & oral hygiene maintenance. The prognosis of each case depends on the severity of periodontal disease and the response to periodontal treatment, while the treatment of affected tooth/teeth with endodontic involvement also requires the same. This review paper is focused on enabling the operator to construct a suitable treatment plan where unnecessary, prolonged or even detrimental treatment is avoided, thus avoiding breaking of Hippocratic Oath taken by a dental surgeon in his/her maiden practice life. DOI: http://dx.doi.org/10.3329/bjdre.v3i1.16594 Bangladesh Journal of Dental Research & Education Vol.3(1) 2013: 36-44